024. Case Report: Giant Cell Tumor Intravertebra - Nababan, Arthur Gospel; Suhendar, Agus (JBN (Jurnal Bedah Nasional), 2024)
Background : Giant cell tumor is a rare neoplasm that most frequently occurs at the end of long bones and accounts for approximately 5% of all primary bone tumors in adults. The prevalence of spinal giant cell tumors is estimated at 2%–15% of all spinal giant cell tumors. However, Giant cell tumor is a rare finding in the spine, especially in the pediatric population. Case : A 6-year-old male patient presented with back pain that had spread to both legs for 1.5 years and had worsened in the past 4 months. The pain is intermittent. The patient also felt tingling in the waist and legs, which then turned into a thickening feeling from the waist to the toes since the last 6 months. The patient also complained of weakness in both legs since 1 year ago. Currently the patient is only on bed rest. The patient cannot walk but can still stand with assistance. Defecation and urination remain within normal limits. History of previous trauma (-) Prolonged cough (-), bed wetting (-), headache (-), seizures (-), decreased consciousness (-), progressive weight loss (-), nausea (-) vomiting (-), history of contact with TB sufferers (-). Conclusion: Complete resection of tumor by laminectomy was performed successfully followed by spinal fusion with a pedicle screw. The screws were placed correctly at all four levels of Vertebrae. The decision was made to give stability for spine and it was scheduled to remove the pedicle screw one year follow-up after surgery. Histopathology results showed characteristic findings of  giant cell tumor.